Scarless deletion of up to seven methyl-accepting chemotaxis genes with an optimized method highlights key function of CheM in Salmonella Typhimurium. - Hoffmann, Stefanie; Schmidt, Christiane; Walter, Steffi; Gerlach, Roman; et al. (PLoS ONE, 2017)
Site-directed scarless mutagenesis is an essential tool of modern pathogenesis research. We describe an optimized two-step protocol for genome editing in Salmonella enterica serovar Typhimurium to enable multiple sequential mutagenesis steps in a single strain. The system is based on the λ Red recombinase-catalyzed integration of a selectable antibiotics resistance marker followed by replacement of this cassette. Markerless mutants are selected by expressing the meganuclease I-SceI which induces double-strand breaks in bacteria still harboring the resistance locus. Our new dual-functional plasmid pWRG730 allows for heat-inducible expression of the λ Red recombinase and tet-inducible production of I-SceI. Methyl-accepting chemotaxis proteins (MCP) are transmembrane chemoreceptors for a vast set of environmental signals including amino acids, sugars, ions and oxygen. Based on the sensory input of MCPs, chemotaxis is a key component for Salmonella virulence. To determine the contribution of individual MCPs we sequentially deleted seven MCP genes. The individual mutations were validated by PCR and genetic integrity of the final seven MCP mutant WRG279 was confirmed by whole genome sequencing. The successive MCP mutants were functionally tested in a HeLa cell infection model which revealed increased invasion rates for non-chemotactic mutants and strains lacking the MCP CheM (Tar). The phenotype of WRG279 was reversed with plasmid-based expression of CheM. The complemented WRG279 mutant showed also partially restored chemotaxis in swarming assays on semi-solid agar. Our optimized scarless deletion protocol enables efficient and precise manipulation of the Salmonella genome. As demonstrated with whole genome sequencing, multiple subsequent mutagenesis steps can be realized without the introduction of unwanted mutations. The sequential deletion of seven MCP genes revealed a significant role of CheM for the interaction of S. Typhimurium with host cells which might give new insights into mechanisms of Salmonella host cell sensing.